The EU Court of Justice in the Process of European Construction and Integration - Piddubna, Viktoriia; Yarotskiy, Vitalii; Pohrebniak, Volodymyr; Popov, Viktor; Klochko, Alona (PRAWO i WIĘŹ, 2025)
The paper is devoted to the evolution of the role and place of the Court of Justice in the process of European integration. The author analyses the relationship between the development of primary European legislation, starting with the Treaty of Paris, and the current stage, following the Treaty of Lisbon. The relevant provisions of the founding treaties and the achievements of the case law at each stage and their impact on integration are examined. Their implications for the shaping of trends in the further development of the activity of the CJEU in the context of the current and upcoming challenges are identified.